Exploration and Research on Higher Mathematics Teaching in Higher Vocational Colleges under New Situation - GUO Hua (Forest Chemicals Review)
Through the in-depth investigation of the main teaching means and methods of higher vocational mathematics teachers, students’ interest in learning higher mathematics and their understanding of higher mathematics, this paper studies the teaching methods and reform ways of Higher Vocational Mathematics under the new situation. In this paper, Walton forest algorithm is used to make statistics and analysis of students’ mathematics learning achievements. In view of many problems and deficiencies found in the survey, this paper puts forward reform and practical suggestions from the aspects of curriculum objectives of higher mathematics curriculum, characteristics of textbook compilation, teaching methods and means, teaching evaluation, teacher team construction and so on. According to the proposed reform plan, some students are tested in the author’s college. The results show that students’ interest in learning higher mathematics has been greatly improved. Students’ mathematical modeling and higher mathematics examination scores have also made great progress. The results show that the method proposed in this paper can improve the teaching quality of higher vocational mathematics classroom.